2017
DOI: 10.1177/1538192717699048
|View full text |Cite
|
Sign up to set email alerts
|

Being and Becoming Men of Character: Exploring Latino and Black Males’ Brotherhood and Masculinity Through Leadership in College

Abstract: This article advances knowledge on the significance of engagement and leadership for five Latino and Black male student leaders at a Hispanic-serving institution. By exploring their experiences in a male-centered initiative, identity and masculinity emerged as salient frames to understand students' engagement on campus. Individual and focus group interviews yielded that relationships and male peer-to-peer bonding built on students' cultural wealth by providing unique opportunities for learning and self-growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Moreover, the goals to which one held a brother accountable was not merely social, academic, or professional, but also theologically specific (e.g., to pray more). These findings confirm the ways brotherhood and its benefits have been conceptualized in previous research studies—as a mutually beneficial social, academic, and paraprofessional community (Brooms 2016; Brooms, Clark, and Smith 2017; Jones and Hotep 2006). In addition, our findings extend this work by considering the ways brotherhood is explicitly constructed via Christian theology toward specified outcomes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the goals to which one held a brother accountable was not merely social, academic, or professional, but also theologically specific (e.g., to pray more). These findings confirm the ways brotherhood and its benefits have been conceptualized in previous research studies—as a mutually beneficial social, academic, and paraprofessional community (Brooms 2016; Brooms, Clark, and Smith 2017; Jones and Hotep 2006). In addition, our findings extend this work by considering the ways brotherhood is explicitly constructed via Christian theology toward specified outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Yet a smaller group of studies focus on one central component of Black male initiatives and organizations (e.g., fraternal life)—brotherhood (Brooms 2016; Brooms, Clark, and Smith 2017; Jones and Hotep 2006). In their investigation of how five Black and Latino student leaders embody brotherhood at a Hispanic-serving institution, Brooms, Clark, and Smith (2017) reported that these students perceived their brotherhood bond to be distinct from fraternities in that they, “don’t throw ragers; we’re here for the genuine well-being of our members” (p. 6). Caring for each other’s well-being was demonstrated through selfless support, being present emotionally, and holding one another accountable for individual growth and academic achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have found that peers have a significant influence on how students experience college (Brooms et al, 2017; Delgado-Guerrero et al, 2014; Strayhorn, 2012). Findings from this study assert the vital importance of Latinx student organizations at PWIs as an important place where Latinx students built relationships with peers who significantly affected their collegiate experience.…”
Section: Discussionmentioning
confidence: 99%
“…Fictive kinship relationships include relationships with individuals who are not related by birth, but who develop reciprocal relationships with social, economic, and political benefits (Fordham, 1996). Brooms et al (2017) found that establishing a brotherhood with other Latino and Black men in college contributed to students’ engagement and leadership development in college for Black and Latino men. Their study suggested that these kinship ties were rooted in a sense of peoplehood that young men established with one another.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation